Different Children, Equal Citizens and a Diverse Team of Teachers: A Safe Space for Unique Persons and Equal Citizens - Avest, I. ter (Journal for the study of religion, 2014)
‘I see no differences between my pupils, I treat them all equal’. This sentence is frequently quoted – a statement that meets approval from most of the teachers and parents. However, a teacher who does not see any difference, won’t be able to acknowledge the uniqueness of each child either. What remains is a classroom full of middle-of-the-road pupils, or – even worse – a classroom full of children of whom at least half of their identity is not visible. In my contribution I argue that it is the difference, the in-equal-ity, that has to be articulated in order to stimulate the development of an authentic worldview of pupils as future citizens in contemporary societies that are characterized by cultural diversity and subsequently different life orientations. Not only the difference between pupils, but even more so the diversity amongst teachers should be promoted to present to pupils a variety of role models as examples of good practice of (future) equal citizenship. The collaboration with Cornelia Roux made me aware of the huge importance and relevance of Human Rights and more specifically Children’s rights. So I start my contribution referring to the Convention on the Rights of the Child in which it is stated that every child has the right to be stimulated in spiritual, moral and social development, and has the right to enjoy the own culture, religion or language. The Vygotskian elaboration on the constructive role of contrasting in-equal-ities for the development of pupils is an important and inspiring source for our plea for ‘teaching and learning ìn difference’. Next to that I ive a brief description of the multicultural character of the Dutch society and its consequences for citizenship education including children’s rights. I will argue that included in ‘freedom of thought, conscience and religion’ is the right to learn from various religious and secular worldview traditions (cf. Morgan 2007); the right to be educated in difference. Awareness of difference stimulates development (Vyggotsky 1978). In a similar way the encounter with the otherness of ‘the other’ challenges the construction of an own authentic worldview. Teachers as role models are of pivotal importance, creating a safe space and a rich learning environment to learn about and from differences in life orientations and from the encounter with ‘the other’ (Arendt 2004; Duyndam & Poorthuis 2005). I present an example of teacher behaviour showing in an RE class on citizenship education that ‘to be different is just normal’ (a vivid example of the child’s right to be different/ unique), and ‘living together: just do it!’ (a vivid example of a teacher’s attitude of openness towards ‘the other’). I conclude with a plea for diversity in teams of teachers representing, acknowledging and actively tolerating cultural and religious diversity – as such exemplifying a safe space of human rights in vivo: teaching and learning ìn difference to become unique persons and equal citizens.Keywords: children’s rights, spiritual development, diversity, (in-)equality, encounter